(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Modern state power is a new aspect of the values of stability, creating conditions for national identity. In this regard, the new social consciousness has come to the forefront in studying the spiritual, social and economic status of the population. Being the main theme of the historical process, the population begins to adapt to the achievement of a specific goal, preserve values and give an idea of the essence of mankind in its development. As a result of the identification of humanity, people enjoy a certain historical authority. He must maintain integrity and establish stability to achieve historical reputation. For the sake of stability, people must not only identify universal human qualities, but also national values and make a significant contribution to its meaning. Any social association is determined by selfconsciousness, and therefore it is a distinctive feature of self-awareness. Symbol of subjective form on a public basis is Kazakhstan’s consciousness. Comparing the consciousness of people and the consciousness of a particular nation, the national consciousness unites with a rational and emotional component. And on the national basis, the sign of the objective form – national behavior and its appearance show that it has an external mentality from other national groups. But there is also a mechanism of social and psychological identity based on national self-awareness and national behavior. The main feature of the formation of the national identity of modern Kazakhstanis is that it can correspond to the ideas of statehood and patriotism, personal freedom and civic values. National identity reflects the need to unite in the formation of national consciousness, taking into account the characteristics of all social groups in society. National identity is one of the fruits of public consciousness and at the same time can influence political consciousness. A person or group can be the subject of political relations, forming a civil position through a national identity, which contributes to the stability of the state. As the state of Kazakhstan passed to a new stage of sovereignty, the issue of the national identity was renewed. The scientific article examines the components of national identity, the relationship between them. National identity is the essence of the nation, the basis of statehood. The study considers the need not to separate a person and ethnicity. Kazakhstan has moved to the next stage of its development, so it is important and significant to note the relevance of the problem of national identity, which is an integral part of spirituality in general. This article examines the components of national identity. National identity is the basis of statehood and national existence. At the same time, human and ethnic ties are considered as a necessity of nationality. Key words: national idea, national identity, national existence, patriotism, political mentality, national characteristics, social stability.